2019
DOI: 10.1371/journal.pone.0214080
|View full text |Cite
|
Sign up to set email alerts
|

ADIPOQ rs2241766 SNP as protective marker against DIBC development in Mexican population

Abstract: BackgroundAdiponectin protein and some variations in its gene, ADIPOQ have recently been associated with cancer because they regulate glucose and lipid metabolism as well as anti-apoptotic and anti-inflammatory proteins.AimThe aim of this study was to analyse the relationship between selected biochemical markers, anthropometric indices and ADIPOQ rs2241766 and rs1501299 SNPs in ductal infiltrating breast cancer (DIBC) in a Mexican population.MethodsThis cross-sectional study included 64 DIBC patients and 167 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…IGF-1 and IGF-2, both endocrine hormones, are responsible for the growth and development of muscles and bones [ 29 ]. ADIPOQ is involved in the regulation of glucose and lipid metabolism and anti-apoptosis, and is directly involved in the growth and development process [ 30 ]. Glycan (GPC) is a membrane proteoglycan containing a glucose-6-phosphate isomerase (GPI) anchor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-1 and IGF-2, both endocrine hormones, are responsible for the growth and development of muscles and bones [ 29 ]. ADIPOQ is involved in the regulation of glucose and lipid metabolism and anti-apoptosis, and is directly involved in the growth and development process [ 30 ]. Glycan (GPC) is a membrane proteoglycan containing a glucose-6-phosphate isomerase (GPI) anchor.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase 1(GPX1) also plays an important role in regulating the growth and development of muscles and has a high expression in muscle tissues [ 35 ]. In summary, through a review of the literature, it was found that the roles of eight key genes in 13 co-expressed genes in growth, development, and meat quality have been confirmed, including PPARD [ 27 ], IGF1 [ 29 ], ADIPOQ [ 30 ], GPC1 [ 31 ], FGFRL1 [ 32 ], SIX1 [ 33 ], MYL2 [ 34 ], and GPX1 [ 35 ]. The role of five genes ( LARGE , CRYAB , LOC10110646 , PLCB1 and CDC42 ) in growth, development, and meat quality has not been extensively studied, and they can be used as candidate genes for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reports no association between ADIPOQ SNPs and BC in American white women [ 25 ]. Genotypes TG and GG of SNP rs2241766 have also been associated with a decreased risk for BC when compared to the TT genotype, the rs2241766 variation with the G allele and the TG and TG + GG genotypes may have a protective effect in ductal infiltrating breast cancer in Mexican women [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variations are also correlated with cancer because of its function in glucose and lipid metabolism. In a Mexican population with ductal infiltrating breast cancer (DIBC), patients with the TT and GT genotypes of the APM1 SNP (rs2241766) showed higher values of WC, hip circumference (HP), and waist-hip ratio (WHR) 58…”
Section: Discussionmentioning
confidence: 99%